2000
DOI: 10.1006/dbio.2000.9666
|View full text |Cite
|
Sign up to set email alerts
|

More Than 95% Reversal of Left–Right Axis Induced by Right-Sided Hypodermic Microinjection of Activin into Xenopus Neurula Embryos

Abstract: In recent years, genes that show left-right (L-R) asymmetric expression patterns have been identified one after another in vertebrate gastrula-neurula embryos. However, we still have little information about when the irreversible L-R specification is established in vertebrate embryos. In this report, we show that almost 100% of the embryos develop to be L-R-inverted larvae after microinjection of activin molecules into the right lateral hypodermic space of Xenopus neurula embryos. After right-side injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…At this stage, left-right orientation of the heart and visceral organs was examined and the incidence of left-right reversal in the injected embryos was scored according to the criteria as previously described (Toyoizumi et al, 1997(Toyoizumi et al, , 2000Mogi et al, 2003). To more precisely judge the gut asymmetry, the laterality of the ventral pancreas was also checked.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, left-right orientation of the heart and visceral organs was examined and the incidence of left-right reversal in the injected embryos was scored according to the criteria as previously described (Toyoizumi et al, 1997(Toyoizumi et al, , 2000Mogi et al, 2003). To more precisely judge the gut asymmetry, the laterality of the ventral pancreas was also checked.…”
Section: Methodsmentioning
confidence: 99%
“…Part of the embryos were photographed after penetrating with 50% glycerol solution. We attached importance to the area and intensity of the expression in the LPM as in our previous papers (Toyoizumi et al, 2000;Mogi et al, 2003). For individual specimen, both LPMs were carefully checked and scored for the laterality of gene expression.…”
Section: Whole-mount In Situ Hybridizationmentioning
confidence: 99%
“…On the one hand, our results indicate that XCR2-dependent activity of neither the nodal family ligands nor their antagonists is essential on the right side for correct patterning. On the other hand, ectopic expression of XCR2 is sufficient to reverse the left-right polarity, as can ectopic expression of TGF␤ family ligands or activated receptors Hanafusa et al, 2000;Hyatt et al, 1996;Sampath et al, 1997;Toyoizumi et al, 2000). Data from several laboratories, including our own, have shown that EGF-CFC proteins function as co-factors for nodal/GDF1 signaling, but are not sufficient to activate SMAD2 signaling in absence of the ligands (Fig.…”
Section: Research Articlementioning
confidence: 77%
“…Our results could suggest that early asymmetry in the node is the consequence of the early left-right mosaic development in the concavity of Rauber's sickle. In Xenopus embryos, microinjection of activin reverses the left-right axis in 95% of the cases (Toyoizumi et al, 2000). It has been shown by Ziv et al (1992) that activin can generate ectopic axial structures in chick blastoderm explants.…”
Section: Discussionmentioning
confidence: 96%